1998
DOI: 10.1007/s002669900199
|View full text |Cite
|
Sign up to set email alerts
|

Nose Surgery (Rhinoplasty) Without External Immobilization and Without Internal Packing: A Review of 812 Cases

Abstract: In a review of 812 cases of rhinoplasty, none of our patients had early bone or septal displacement; swelling, bruising, and pain were almost nonexistent. This confirms that an external splint would not have been of any benefit in these cases. Packing should help prevent epistaxis, synechiae, and early bone and septal displacement. Not using any packing, we have not encountered these complications. Besides, we have not seen a single submucosal hematoma or a septal necrosis. Therefore, we doubt the value of pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
4
5
0
Order By: Relevance
“…Splint is used to immobilize the bone and septum and to decrease the pain and swelling. Our results are the same as the results of Camirand 41 and Camirand et al 42 , because there were no bone and septal displacements or excessive pain and swelling. The placement of adhesive sterile skin tapes was quite enough for adequate nose fixation, because the nose does not have joints.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Splint is used to immobilize the bone and septum and to decrease the pain and swelling. Our results are the same as the results of Camirand 41 and Camirand et al 42 , because there were no bone and septal displacements or excessive pain and swelling. The placement of adhesive sterile skin tapes was quite enough for adequate nose fixation, because the nose does not have joints.…”
Section: Discussionsupporting
confidence: 91%
“…Nasal packing is used to maintain immobilization and hemostasis, to prevent bleeding, septal hematoma and necrosis as well as to prevent synechiae between the septum and lateral nasal wall. Our results differ from those of Guyuron 39 , but they are the same as results of many other researchers [41][42][43][44][45][46][47][48][49][50][51] because postoperative bleeding occurred in only 1 patient on the day 10 after surgery, when the most surgeons already removed internal packing. Also, there were no cases of the bone and septal displacements, septal hematoma, septal necrosis and synechiae.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…29 In yet another study by Camirand et al, septoplasty was suggested to avoid even the external immobilization of the nose. 30,31 …”
Section: Discussionmentioning
confidence: 99%